Using the right recipe for cooking rice reduces toxic inorganic arsenic content - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
The content of toxic arsenic in rice not only depends on where you get the rice but also how you seen it; that is the result of a new study performed by a UK research group.